The Analysis Study of Gender and Risk of Congenital Hypothyroidism : A Comprehensive Systematic Review - Pasambo, Trisnawanta Asih; Saleh, Hendra; Akbar, Rafiqa Rais (The International Journal of Medical Science and Health Research, 2024)
Background: Congenital hypothyroidism is defined as a deficiency of thyroid hormone at birth and is one of the most common endocrine disorders in newborns. Congenital hypothyroidism, with a prevalence of 1 in 3000-4000 live births, is the most common preventable cause of mental retardation in children. The aim: The aim of this study to show about gender and risk of congenital hypothyroidism. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: many risk factors are involved in the development of congenital hypothyroidism in children. It should be noted that the irreversible consequences of this disease for children including mental retardation is one of the cases which to control and remove it. Accordingly, awareness of the birth season could help policymakers who plan preventive programs to reduce the false negative results among neonates, especially girls.